Using the Water Quality Index as a Powerful Tool to Assess the Water Quality for Drinking Purposes in Al-Salam, Western Region of Baghdad City, Iraq - Jalal N. Jeber (Journal of Global Pharma Technology, 2016)
Background: Tap waters play an important role in fulfilling the people needs for drinking and domestic purposes. Contaminate the tap water with different pollutants has become an issue of great concern for 90% of people who are depended on the tap water as the main source of drinking. Pollutants can make their way easily into the delivering pipes which suffer from the leaking resulting in decreasing the quality of water. Objective: Therefore, assess the water quality for drinking purpose by calculating the water quality index is an important tool to ascertain whether the water is suitable for human consumption or not. Methods: In the present work, the water quality of the Al-Salam, western region of Baghdad city, Iraq was investigated for 7 months (Jan-July 2017). 63 tap water and 7 water station samples were collected and analyzed using standard methods. The index proposed measuring nine parameters which are: TDSs, pH, TH, DO, phosphates, nitrates, temp, BOD5, fecal coliform, turbidity and conductivity. The calculated values of parameters were normalized into the scale (0-100) and converted to the quality rating statements (Excellent, good, medium, bad and very bad). Results: The results show that WQI values of the tap water samples have ranged from 64- 83% while it ranged from 88-94 for the water station samples. Also, it can notice that none of the water samples is recorded WQI=100 during the entire period of the study. The proposed NFS index was able to determine the water quality and it presents an accurate, rapid and modern way to evaluate and monitor the water quality.Keywords: Water quality index, Drinking water, Pollution.